PENGARUH PENGGUNAAN MEDIA GAMBAR BERSERI TERHADAP KETERAMPILAN BERBICARA SISWA KELAS V SD NEGERI 257 GATTARENG KECAMATAN SALOMEKKO KABUPATEN BONE - Sudarto, Sudarto; Rosmalah, Rosmalah; Kurniati, Kurniati (Journal of Innovation Research and Knowledge, 2024)
This research is a pre-experimental research which aims to determine whether there or there is not an influence of using serial image media on the speaking skills of the Fifth Grade students at SD Negeri 257 Gattareng, Salomekko District, Bone Regency. The population in this research were all the Fifth Grade students at SD Negeri 257 Gattareng with a sample of 23 students selected based on saturated sampling techniques. The data collection technique used was a non-test to determine the students' speaking skills before and after using serial image media. The data analysis used is a descriptive and an inferential statistical analysis. Based on the results of descriptive statistical analysis, the pretest average was of 39.87, while the posttest average was of 74.78. The data obtained was then analyzed using a paired difference test (paired sample t-test) with a significance level of 5%. From the results of data analysis, it was obtained that tcount was of 19.537 > ttable was of 2.0737. So H0 is rejected and H1 is accepted. Conclusion: the use of serial image media has a significant effect to the students' speaking skills